Keep sharp : build a better brain at any age - Gupta, Sanjay, 1969- (New York, NY : Simon & Schuster, 2020)
"Throughout our life, we look for ways to keep our mind sharp and effortlessly productive. Now, globetrotting neurosurgeon Dr. Sanjay Gupta offers insights from top scientists all over the world, whose cutting-edge research can help you heighten and protect brain function and maintain cognitive health at any age. Keep Sharp debunks common myths about aging and cognitive decline, explores whether there's a "best" diet or exercise regimen for the brain, and explains whether it's healthier to play video games that test memory and processing speed, or to engage in more social interaction. Discover what we can learn from "super-brained" people who are in their eighties and nineties with no signs of slowing down-and whether there are truly any benefits to drugs, supplements, and vitamins. Dr. Gupta also addresses brain disease, particularly Alzheimer's, answers all your questions about the signs and symptoms, and shows how to ward against it and stay healthy while caring for a partner in cognitive decline. He likewise provides readers with a personalized twelve-week program featuring practical strategies to strengthen your brain every day. Keep Sharp is the only owner's manual you'll need to keep your brain young and healthy regardless of your age!"--
Includes bibliographical references and index.
Keywords: Aging -- Prevention